Monitoring, Evaluation and Accountability Against Corruption: A South African Case Study - Mantzaris, E.A.; Pillay, P. (Journal of Reviews on Global Economics, 2019)
The article is an empirical effort to research and analyse the dialectical relationship between public sector monitoring and evaluation relations, structures and processes with corruption and accountability. The case study is the Gauteng Department of Health that has been the subject of this research for the last two years as a part of a wider health-related project. Following a brief exposition of the concept of monitoring and evaluation that has been covered extensively in international and national literature, its relationship with accountability is explored. The existing legislative national and provincial legislature as well as the existing state rules and regulations are presented before the description of the project’s research methods and design. This is a research project utilising a qualitativeâ€“based research design and framework consisting of thorough content analysis of primary and secondary sources including government official documents, newspaper articles and face-to-face interviews with a wide range of carefully selected public administrators, political figures and representatives of the public sector. The paper presents an analysis of corruption trends within the department as identified in the latest Auditor General’s report, a corruptionâ€“ridden case and the wide-ranging responses of the interviewees. The latest evidenceâ€“based Corruption Index follows.